Práticas de gestão da qualidade na relação cliente-fornecedor em produtos eletrônicos - Zorzenon, Rafael (Universidade Federal de São Carlos, 2019)
The electronics industry, as a driver of most other sectors, has been gaining prominence in recent years. The opening of trade barriers has made the market more competitive, which is why it requires a new look at quality management in the supply chain (GQCS), which has a systemic approach and aims to improve performance throughout the supply chain. through quality management. The main objective of this work was to evaluate the practices adopted by organizations according to the theory of quality management in the supply chain in the customer-supplier relationship, in particular in an electronic-electric product supplier. From the Systematic Bibliographic Review (RBS), nine main areas related to GQCS have been identified: Communication and partnership; strategy; Quality tools; process management; customer and market focus; supplier relationship management; information and analysis of quality data; management of human resources and innovation, continuous improvement and product design, and according to the main objective of the work was focused on the area of relationship management with suppliers. The data were collected using a semistructured interview conducted in an automotive engine manufacturer and an electronic component supplier, both located in the state of São Paulo, as a main instrument, so it is not possible to generalize the results, but to show the existing relationship . Through the case study carried out, it was possible to identify several present practices, highlighting the measurement and analysis of performance indicators as the main motivator in the search for the improvement of quality in organizations, as well as it was observed that the practices of incentive for improvement the quality of the products received from the suppliers and the joint elaboration of actions and improvement projects require a greater strengthening and incentive by the organizations in order to contribute to the quality improvement in this customer-supplier relationship.
Quality management practices in the customer-supplier relation in electronic products
Keywords: Cadeia de suprimentos; Gestão da cadeia de suprimentos; Gestão da qualidade; Gestão da qualidade na cadeia de suprimentos; Práticas de gestão da qualidade na cadeia de suprimentos; Supply chain; Supply chain management; Quality management; Supply chain quality management; Practices of quality management in the supply chain; ENGENHARIAS::ENGENHARIA DE PRODUCAO::GERENCIA DE PRODUCAO